2011
DOI: 10.1016/j.ygyno.2011.07.099
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized trial of integrative medicine for women with ovarian cancer

Abstract: Objectives Despite increased use of integrative medicine in cancer therapy, little data exist on its efficacy. This prospective, randomized, pilot trial sought to evaluate the feasibility of combined modality integrative medicine (CM-IM) in women with ovarian cancer (OvCA) and evaluate its effects on quality of life (QoL), chemotherapy toxicity and immunologic profiles. Methods Women with newly diagnosed OvCA requiring chemotherapy were offered enrollment. Those randomized to the experimental arm received hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…[1][2][3] In recognition of this, we are expanding our program and focusing on reasons why patients avoid complementary therapies including resource barriers, fear, and concerns with toxicity. Although data support that alternative therapies are increasingly being used by cancer patients, more evidence supporting these therapies is required due to the paucity of data and the often conflicting nature of reports.…”
Section: To the Editormentioning
confidence: 99%
“…[1][2][3] In recognition of this, we are expanding our program and focusing on reasons why patients avoid complementary therapies including resource barriers, fear, and concerns with toxicity. Although data support that alternative therapies are increasingly being used by cancer patients, more evidence supporting these therapies is required due to the paucity of data and the often conflicting nature of reports.…”
Section: To the Editormentioning
confidence: 99%
“…This same study also found significant improvement in depressed mood among those participants receiving the HT intervention. Judson et al [ 24 ] found a trend for improvement in immunological profiles among ovarian cancer patients treated with an integrative therapy package (including HT) during chemotherapy treatment and conclude that the intervention warrants further investigation. Gronowicz et al [ 8 ] utilized Therapeutic Touch (bioenergy) in a breast cancer mouse model with 4T1 modified 66c14 (highly metastatic to lymph nodes breast cancer cell line) and was able to demonstrate significant downregulation of specific lymphocytes, macrophages, and serum cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Cada vez mais pessoas com câncer, especialmente mulheres com câncer, estão recorrendo à MI para atender às necessidades não atendidas durante a terapia convencional. Alguns autores relatam que até 80% de todas as pessoas com câncer e 44% dasJUDSON et al, 2011;NATIONAL CENTER FOR COMPLEMENTARY AND INTEGRATIVE HEALTH, 2020).Considerando o que foi posto acima, o marco teórico desse estudo é o da MedicinaIntegrativa no contexto dos cuidados paliativos, para uma melhor compreensão do seu papel na definição, evidências e elaboração de projetos para aplicação dentro desses centros de…”
unclassified
“…sistemas médicos completos, medicina mente-corpo, práticas baseadas na biologia, práticas manipulativas e corporais e medicina energética(JUDSON et al, 2011).Na figura 1 são encontradas as seguintes terminologias referentes à Medicina Integrativa:Figura 4 -Termos utilizados para Medicina Integrativa na Literatura. Fonte: Hirayama (2016).O Consórcio Acadêmico para Medicina Integrativa e Saúde dos Estados Unidos (2020, on-line) define MI como a prática da medicina que reafirma a importância da relação entre médico e paciente, enfoca a pessoa como um todo, é informado por evidências e faz uso de todas as abordagens terapêuticas e de estilo de vida adequadas, profissionais de saúde e disciplinas para alcançar a saúde e a cura ideais.…”
unclassified
See 1 more Smart Citation